Baryon content in a sample of 91 galaxy clusters selected by the South Pole Telescope at 0.2 <z < 1.25. Issue 3 (16th May 2018) - Chiu, I; Mohr, J J; McDonald, M; Bocquet, S; Desai, S; Klein, M; Israel, H; Ashby, M L N; Stanford, A; Benson, B A; Brodwin, M; Abbott, T M C; et al.
ABSTRACT: We estimate total mass ( M 500 ), intracluster medium (ICM) mass ( M ICM ), and stellar mass ( M ⋆ ) in a Sunyaev–Zel'dovich effect (SZE) selected sample of 91 galaxy clusters with masses M 500 ≳ 2.5 × 10 14 M⊙ and redshift 0.2 < z < 1.25 from the 2500 ^2 South Pole Telescope SPT-SZ survey. The total masses M 500 are estimatedfrom the SZE observable, the ICM masses M ICM are obtained from the analysis of Chandra X-ray observations, and the stellar masses M ⋆ are derived by fitting spectral energy distribution templates to Dark Energy Survey griz optical photometry and WISE or Spitzer near-infrared photometry. We study trends in the stellar mass, the ICM mass, the total baryonic mass, and the cold baryonic fraction with cluster halo mass and redshift. We find significant departures from self-similarity in the mass scaling for all quantities, while the redshift trends are all statistically consistent with zero, indicating that the baryon content of clusters at fixed mass has changed remarkably little over the past ≈9 Gyr. We compare our results to the mean baryon fraction (and the stellar mass fraction) in the field, finding that these values lie above (below) those in cluster virial regions in all but the most massive clusters at low redshift. Using a simple model of the matter assembly of clusters from infalling groups with lower masses and from infalling material from the low-density environment or field surrounding the parent haloes, we show that the measured mass trends without strong redshift trends in the stellar mass scaling relation could be explained by a mass and redshift dependent fractional contribution from field material. Similar analyses of the ICM and baryon mass scaling relations provide evidence for the so-called 'missing baryons' outside cluster virial regions.